Modulation of Cellular Circadian Rhythms by Secondary Metabolites of Lichens - Srimani, Soumi; Schmidt, Cosima Xenia; Gómez-Serranillos, Maria Pilar; Oster, Henrik; Divakar, Pradeep K. (Frontiers in Cellular Neuroscience, 2022)
Background: Most mammalian cells harbour molecular circadian clocks that synchronize physiological functions with the 24-hour day-night cycle. Disruption of circadian rhythms, through genetic or environmental changes, promotes the development of disorders like obesity, cardiovascular diseases, and cancer. At the cellular level, circadian, mitotic, and redox cycles are functionally coupled. Evernic (EA) and usnic acid (UA), two lichen secondary metabolites, show various pharmacological activities including anti-oxidative, anti-inflammatory, and neuroprotective action. All these effects have likewise been associated with a functional circadian clock. Hypothesis/ purpose: To test, if the lichen compounds EA and UA modulate circadian clock function at the cellular level. Methods: We used three different cell lines and two circadian luminescence reporter systems for evaluating dose- and time-dependent effects of EA/UA treatment on cellular clock regulation at high temporal resolution. Output parameters studied were circadian luminescence rhythm period, amplitude, phase, and dampening rate. Results: Both compounds had marked effects on clock rhythm amplitudes and dampening independent of cell type, with UA generally showing a higher efficiency than EA. Only in fibroblast cells, significant effects on clock period were observed for UA treated cells showing shorter and EA treated cells showing longer period lengths. Transient treatment of mouse embryonic fibroblasts at different phases had only minor clock resetting effects for both compounds. Conclusion: Secondary metabolites of lichen alter cellular circadian clocks through amplitude reduction and increased rhythm dampening.